Eye-movement patterns are associated with communicative competence in autistic spectrum disorders. - Norbury, C; Brock, J; Cragg, L; Einav, S; Griffiths, H; Nation, K (2009)
BACKGROUND: Investigations using eye-tracking have reported reduced fixations to salient social cues such as eyes when participants with autism spectrum disorders (ASD) view social scenes. However, these studies have not distinguished different cognitive phenotypes. METHODS: The eye-movements of 28 teenagers with ASD and 18 typically developing peers were recorded as they watched videos of peers interacting in familiar situations. Within ASD, we contrasted the viewing patterns of those with and without language impairments. The proportion of time spent viewing eyes, mouths and other scene details was calculated, as was latency of first fixation to eyes. Finally, the association between viewing patterns and social-communicative competence was measured. RESULTS: Individuals with ASD and age-appropriate language abilities spent significantly less time viewing eyes and were slower to fixate the eyes than typically developing peers. In contrast, there were no differences in viewing patterns between those with language impairments and typically developing peers. Eye-movement patterns were not associated with social outcomes for either language phenotype. However, increased fixations to the mouth were associated with greater communicative competence across the autistic spectrum. CONCLUSIONS: Attention to both eyes and mouths is important for language development and communicative competence. Differences in fixation time to eyes may not be sufficient to disrupt social competence in daily interactions. A multiple cognitive deficit model of ASD, incorporating different language phenotypes, is advocated.